Tensile Properties and Impact Toughness of AlCoxCrFeNi3.1–x (x = 0.4, 1) High-Entropy Alloys - Zhang, Lu; Zhang, Yong (Frontiers in Materials, 2020)
In this work, AlCoxCrFeNi3.1–x (x = 0.4, 1) high-entropy alloys (HEAs) were investigated. The effects of different Co and Ni content (both of which are FCC stabilizers with similar atomic radii) on the microstructure and mechanical properties of the system were studied with the goal of improving the cost-effectiveness of the alloys. AlCo0⋅4CrFeNi2⋅7 and AlCoCrFeNi2⋅1 were prepared via vacuum induction melting. X-ray diffraction and scanning electron microscope results demonstrated that an FCC+B2 structure formed. Additionally, tensile tests at room temperature and impact tests at 77, 200, and 298 K were also carried out. From the results, it could be determined that the tensile properties of the tested samples were similar. The impact toughness of AlCo0⋅4CrFeNi2⋅7 with a V-notch was 21.77 J at 298 K, and this was more than three times larger than that of AlCoCrFeNi2⋅1. Compared with the Al0⋅3CoCrFeNi and Al0⋅1CoCrFeNi FCC structured HEAs, AlCoxCrFeNi3.1–x alloys showed low impact toughness but had a high yield strength.